1992
DOI: 10.1111/j.1398-9995.1992.tb02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological effects of immunotherapy with alum‐absorbed grass allergoid in grass‐pollen‐induced hay fever

Abstract: A double-blind, placebo-controlled study of immunotherapy was conducted in 19 patients with grass-pollen hay fever to evaluate the efficacy and safety of a formalinized depot grass allergoid. The patients were assessed before and during IT by clinical (symptom-medication scores during the grass- pollen season, specific nasal and skin reactivity) and immunological (specific IgE, IgG, IgG1 and IgG4 antibodies) parameters. High doses of grass allergoid, corresponding to a cumulative pre-seasonal dosage of 46,050 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 28 publications
3
39
0
4
Order By: Relevance
“…However, results of specific IgE levels were inconsistent after SIT with different allergoids. For example, Guerra et al [35] reported no change in specific IgE levels 1 year after pollen allergoid immunotherapy, whereas Pastorello et al [36] observed a significant increase in mean specific IgE levels after 3 and 4 months of pollen SCIT. Keskin et al [13] did not detect any differences in grass pollen-specific IgE between levels at baseline and after 1 year of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of specific IgE levels were inconsistent after SIT with different allergoids. For example, Guerra et al [35] reported no change in specific IgE levels 1 year after pollen allergoid immunotherapy, whereas Pastorello et al [36] observed a significant increase in mean specific IgE levels after 3 and 4 months of pollen SCIT. Keskin et al [13] did not detect any differences in grass pollen-specific IgE between levels at baseline and after 1 year of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies can be subdivided into 13 studies (5,7,9,11,12,15,17,19,22,32,35,36,39) investigating ragweed allergy (nine showing clinically relevant efficacy, i.e., symptom/medication scores diminished by >30% in the actively treated). Fifteen studies investigated the efficacy of immunotherapy in grass-pollen allergy (8,13,16,18,20,21,23,25,30,34,37,38,40,44,47), of which 14 proved efficacy. Nine studies investigated other pollen allergens: mountain cedar (10,27,29), Parietaria (42,43,46), Cupressus (45), Cocos (41), and mixtures (6); efficacy was demonstrated in six.…”
Section: Clinical Efficacy Of Immunotherapy In Rhinitismentioning
confidence: 99%
“…The main reasons for excluding studies were lack of double-blinding/ randomization, review articles, multiple allergen extracts, outcomes unrelated to efficacy and preparations that are not commercially available. These criteria excluded early allergoid studies (51)(52)(53)(54)(55), a study with a recombinant allergen (which is not commercially available) (56), a paediatric SCIT study in which a combined asthma symptom-medication score was the primary outcome measure (57) and, regretfully, the 'Preventive Allergy Treatment' (PAT) study (58). Even though the 10-year PAT study was well designed and asked an important clinical question (does SCIT for allergic rhinoconjunctivitis prevent the development of asthma?…”
Section: Resultsmentioning
confidence: 99%